2016
DOI: 10.1007/s12593-013-0101-7
|View full text |Cite
|
Sign up to set email alerts
|

Free Tissue Transfer and Replantation in Pediatric Patients: Technical Feasibility and Outcome in a Series of 28 Patients

Abstract: Microsurgery in the pediatric population is still challenging because of technical difficulties in the small vessel diameter anastomosis and flaps dissection. The present study reports our experience of microsurgical reconstruction with free tissue transfer and replantation. Twenty-eight pediatric patients under the age of 15 years underwent different microsurgical procedures over a 10-year period. Twenty-one patients (75 %) underwent elective free tissue transfer, while emergency replantation was done in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 32 publications
1
39
0
1
Order By: Relevance
“…On the other hand, still other studies have suggested that pediatric vessels are not prone to vasospasm . Aboelatta and Aly reported that patients 5 to 10 years of age present greater challenges in terms of surgical technique; patients under 5 years have more problems with flap outcomes; and patients over 10 years can undergo microsurgical procedures similar to adults. Serletti et al reported that vessel characteristics of children between 13 and 17 years of age are closer to those of adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, still other studies have suggested that pediatric vessels are not prone to vasospasm . Aboelatta and Aly reported that patients 5 to 10 years of age present greater challenges in terms of surgical technique; patients under 5 years have more problems with flap outcomes; and patients over 10 years can undergo microsurgical procedures similar to adults. Serletti et al reported that vessel characteristics of children between 13 and 17 years of age are closer to those of adults.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of microsurgery for free flap transfer is commonly used in head and neck reconstructions at many centers . Although free flap transfer in pediatric patients presents many challenges, there have been many series published in the past 20 years demonstrating the safety and reliability of free flap transfer in such patients and its increasing use in head and neck reconstruction …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La transferencia libre de tejido en niños, usualmente no presenta los factores de riesgo que sí enfrentamos en los adultos como son: el tabaquismo, y la enfermedad vascular periférica lo que por sí solo debe traducirse en una mejor posibilidad de éxito en este grupo, si sumado a esto, cuidamos los aspectos antes mencionados en relación al manejo de los vasos, no debiera asombrarnos las buenas cifras de éxito publicadas internacionalmente 14,15 . Sin embargo, hay temas que merecen una consideración especial y aún no han sido totalmente analizados: el efecto del crecimiento y desarrollo en el tejido trasplantado, así como las repercusiones psicológicas secundarias y la discapacidad a tan temprana edad de la zona dadora 16 .…”
Section: A B Discusiónunclassified
“…The accompanying vein or veins are used for the flap drainage as a rule; a few authors recommend adding the great saphenous vein for venous drainage; in 6 of 25 ALT flaps, anastomosis to the great saphenous vein as the second venous drainage was done. 17 22 The practice of performing two venous anastomosis seems to be not standard; certainly, the latissimus dorsi and the rectus abdominis afford the scope of a single venous anastomosis, 23 whereas with most ALT flaps 2 anastomosis could be done.…”
Section: Introductionmentioning
confidence: 99%